Evaluation of Nephroprotective Efficacy of Hypoxic Preconditioning in Patients Undergoing Coronary Artery Bypass Surgery; Cardiorenal Medicine; Vol. 6, iss. 4 - Vesnina Zh. V. Zhaneta Vladimirovna; Lishmanov Yu. B. Yury Borisovich; Nesterov E. A. Evgeny Alexandrovich; Aleksandrova Е. А. Ekaterina Aleksandrovna (2016, 2016)
Title screen